PELAKSANAAN SUPERVISI PEMBELAJARAN MELALUI KEGIATAN PENDAMPINGAN DI UPTD SMP NEGERI 3 TOBADAK KABUPATEN MAMUJU TENGAH - Simbala, Wardiyanto; Wahira; Muhammad Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning supervision is an important component in developing teacher competence to optimize the learning process. The implementation of the Merdeka Curriculum demands a reorientation of supervision from conventional hierarchical approaches toward more collaborative and empowering coaching and mentoring approaches. This study aims to understand the implementation of learning supervision through mentoring activities and identify supporting and inhibiting factors in its implementation at UPTD SMP Negeri 3 Tobadak, Mamuju Tengah Regency. This study employed a qualitative approach with descriptive case study research design. Data collection was conducted through observation, in-depth interviews, and documentation. Research subjects included the principal, vice principal for curriculum affairs, and teachers. Data analysis used the Miles, Huberman, and Saldana model. The results show that learning supervision is implemented through coaching and mentoring approaches in three main stages: pre-observation, observation, and post-observation. Supporting factors include high teacher motivation and collaboration, availability of technology infrastructure, the principal as a Technology Ambassador role model, and effective school learning communities. Inhibiting factors include teacher activities outside their main duties, unconducive school environment conditions, and limited internet connectivity. This study concludes that learning supervision with coaching and mentoring approaches proves effective in improving teacher competence and learning quality.